ТЕРМІНОЛОГІЧНІ АСПЕКТИ ПІДВИЩЕННЯ ТЕМПЕРАТУРИ ТІЛА У ДІТЕЙ - Волосовець, О. П.; Кривопустов, С. П.; Кузьменко, А. Я.; Кривопустова, М. В. (Українські медичні вісті, 2023)
ТЕРМІНОЛОГІЧНІ АСПЕКТИ ПІДВИЩЕННЯ ТЕМПЕРАТУРИ ТІЛА У ДІТЕЙ